A Rare Case of Anaplastic Lymphoma Kinase-Positive Large B-Cell Lymphoma Involving Epidural Tissue. (9th November 2022) - Satia, S; Lam, J
Abstract: Introduction/Objective: Anaplastic lymphoma kinase-positive large B-cell lymphoma (ALK-positive LBCL) is a rare, aggressive type of non-Hodgkin's B-cell lymphoma with characteristic rearrangements and overexpression of ALK. Diagnosis of ALK-positive LBCL is challenging because of its rarity and uncharacteristically low expression of B- lineage antigens usually needed for diagnosis of B-cell lymphomas. In this report, we describe a case of ALK-positive large B cell lymphoma involving epidural soft tissue in a young adult. Methods/Case Report: 29 year old presented to emergency department with a two week history of back pain and a three day history of worsening numbness and weakness in the lower extremities. MRI of the thoracic spine showed an epidural soft tissue mass posterior to T5, T6 and T7 vertebral bodies with abnormal signal in the T6 spinous process. Histological examination from the epidural mass revealed sheets of atypical lymphoid cells with abundant pale cytoplasm and round vesicular nuclei with prominent single to occasional multiple nucleoli. Immunohistochemical stains demonstrated neoplastic cell positivity for ALK, VS38c, CD138, EMA, MUM1, CD45, PAX5 and MCK. They were negative for CD3, CD20, CD19, CD79a, CD30, CD2, CD117, SOX10, HMB45, cytokeratin, synaptophysin and chromogranin. These overall findings were consistent with ALK-positive large B-cell lymphoma. Results (if a Case Study enter NA): NA. Conclusion: ALK-positive large B-cell lymphoma is a non-Hodgkin lymphoma associated with high morbidity and mortality. Absence of reliable B-cell marker expression in this B-cell lymphoma requires recognition of morphological findings to order confirmatory testing such as immunohistochemical stains for CD138 and ALK. This particular case also showed an unusual anatomic presentation in epidural tissue.